Development of RAPD-SCAR markers for Lonicera japonica Thunb. (Caprifolicaceae) variety authentication by improved RAPD and DNA cloning - Yang, Luquan; Khan, Md. Asaduzzaman; Mei, Zhiqiang; Yang, Manman; Zhang, Tiandan; Wei, Chunli; Yang, Weichan; Zhu, Li; Long, Yan; Fu, Junjiang (Revista de Biología Tropical, 2014)
Genetic diversity within a species is a common feature, which plays a vital role in its survival and adaptability, and is important for the identification and authentication of a species. Lonicera japonica is a traditionally used medicinal plant, which have been recently genetically characterized by an improved random ampliﬁed polymorphic DNA (RAPD) analysis. In this study, the molecular markers on the basis of these RAPD fragments have been developed to identify specific L. japonica variety. The DNAs were extracted from fresh young leaves of different samples of L. japonica collected from Shenzhen, Yichang, Leshan, Emei and Loudi, China. The DNA materials were amplified using improved RAPD PCR. Different RAPD bands were excised, cloned and developed for stable sequence-characterized amplified region (SCAR) markers with different species. Two SCAR markers, JYH3-3 and JYH4-3, have been successfully cloned from improved RAPD fragments. The SCAR marker JYH3-3 was found specific for all of the L. japonica samples collected from the different regions, and another marker JYH 4-3 was strictly specific to the Shenzhen sample from Guangdong province, which is geographically distant from Hubei, Sichuan and Hunan Provinces (source of other L. japonica samples). The marker JYH3-3 was found as specific molecular marker for the identification of L. japonica, while JYH4-3 was found as molecular marker strictly specific for the Shenzhen sample. The developed SCAR markers might serve as more specific molecular markers for L. japonica variety authentication. The combination of improved RAPD analysis and SCAR marker development have resulted useful tools to study the genetic variety of any organism, which we have successfully applied here in L. japonica. de cualquier organismo, que hemos aplicado con éxito en L. japonica.